Carbothermic reduction of chalcopyrite without polluting emission - Lovera Dávila, Daniel (2000)
In the context of clean technologies is not only important to maximize production , minimize costs, but also not pollute the environment , it is for that reason we must develop basic research leading to mitigate SO2 to prevent air pollution. Direct reduction of sulfides is of interest in the metallurgical field for the base metal , using a desulfurizer agent ( CaO, CaCO3 and Na2CO3) , this being a friendly metal production route. In this paper , we show the results of research in the direct reduction of chalcopyrite with carbon in the presence of lime, as a possibility to produce copper from a sulfide avoiding air pollution. ; Also their effect on the reacted fraction and temperature the reaction rate , reaction time , molar ratios of reactants : the effect of the variables involved in the carbothermic reduction was studied . Besides modeling the reduction kinetics of chalcopyrite describing the experimental data very well in the temperature range 800 1100 ° shown _ C.